Do-It-Yourself (DIY) Assistive Technology: A Communication Board Case Study. - Hamidi, Foad; Baljko, Melanie; Kunic, Toni; Feraday, Ray (Springer Nature, 2014)
Do-It-Yourself (DIY) and open design approaches allow for the development of customized, affordable assistive technologies. Freely shared designs and software components open doors for new ways to create and to share technology, representing an approach that has the potential to be more efficient, affordable, and effective than commercial approaches to Assistive Technology development and deployment. In this paper, we present a case study of how these methods have been used to develop a DIY, open-source Speech-Generating Device.
International Conference on Computers for Handicapped Persons, ICCHP 2014: Computers Helping People with Special Needs, Springer, Cham